2008
DOI: 10.3141/2077-11
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Challenges to Implementing Transit-Oriented Development in China

Abstract: Several Chinese cities are interested in incorporating transit-oriented development (TOD) around their subway stations. Few cities, however, have considered incorporating TOD into their bus systems; fewer still have included China's bike population. The midsize Chinese city of Jinan, capital of the northeastern province of Shandong, wants to incorporate both bus rapid transit (BRT) and TOD within its urban planning framework. Jinan is set to construct a 135-km BRT network and seeks to incorporate TOD initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Moreover, longer commute times not only make residents feel physically exhausted but also reduce their SWB. We also found that residents who walk or ride a bike to work Transportation have significantly less sense of happiness than commuters using motor vehicles, which may be related to the imperfect walkways and bicycle lanes in China, where many cities give priority to motor vehicles in road construction (Thomas and Deakin 2008;Pucher et al 2007). Motorway and pedestrian/bike lanes are often mixed, which reduces the safety and pleasure of people walking or cycling.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, longer commute times not only make residents feel physically exhausted but also reduce their SWB. We also found that residents who walk or ride a bike to work Transportation have significantly less sense of happiness than commuters using motor vehicles, which may be related to the imperfect walkways and bicycle lanes in China, where many cities give priority to motor vehicles in road construction (Thomas and Deakin 2008;Pucher et al 2007). Motorway and pedestrian/bike lanes are often mixed, which reduces the safety and pleasure of people walking or cycling.…”
Section: Discussionmentioning
confidence: 83%
“…After careful reading of the abstracts, we were able to identify 15 studies on TOD in China (listed in Table 1) that offer first-hand empirical evidence. (Thomas & Deakin, 2008) x Land use data Jinan (Yang, et al, 2016a) x Land development data Shenzhen (Yang et al, 2016b) x Land transaction data Beijing (Zhang, Meng, Wang, & Xu, 2014) x Housing price data Beijing (Zhang & Wang, 2013) x Housing price data Beijing…”
Section: Tod In Chinamentioning
confidence: 99%
“…Rodriguez, Vergel-Tovar, and Camargo (2016) showed Downloaded by [UC Berkeley Library] at 19:33 04 November 2017 that building activity measured as added floor area and construction permits increased after the implementation of BRTs in Bogota and Quito (Ecuador), although the effects varied based on location and land use. In Jinan (China), the oversupply of auto-oriented land uses, midblock crossings on the corridor, lack of pedestrian infrastructure and connectivity, and parking issues were barriers to the introduction of BRT-oriented development (Thomas and Deakin 2008). In Seoul (Korea), even though the BRT contributed to increases in development density among urban centers, there were limited effects on residential property values within the influence area of the system (Jun 2012).…”
Section: Brt and Urban Developmentmentioning
confidence: 99%